Isolation and biological characterization of a novel type of pulmonary mesenchymal stem cells derived from Wuzhishan miniature pig embryo. (1st August 2016) - Ma, Caiyun; Guo, Yu; Liu, Hao; Wang, Kunfu; Yang, Jinjuan; Li, Xiangchen; Liu, Changqing; Guan, Weijun
Abstract: Pulmonary mesenchymal stem cells (PMSCs) have great potential in lung tissue engineering and represent attractive candidates for disease treatment in human and veterinary research. However, a reliable method for isolation and localization of porcine PMSCs in situ is still uncertain. In this study, we successfully isolated PMSCs from Wuzhishan miniature pig embryos in vitro and also attempted to unravel its fundamental differentiation potential and biological characteristics. The isolated PMSCs, which could be cultured and passaged for at least 15 passages, exhibited a typical fibroblast‐like morphology and high proliferative potential. Moreover, the PMSCs could express pluripotent marker genes (Oct4 and Nanog) and MSCs‐related surface antigens ( β ‐integrin, CD44, CD71, CD73, CD90, and CD105), while the expressions of CD34 and CD45 were negative. Cell cycle examination showed that the rate of G0/G1 was about 72.1–90.2%. Additionally, the PMSCs not only could be induced to transdifferentiate into mesoblastic cells such as osteoblasts, chondrocytes, and adipocytes in vitro, but also the neural ectoderm and endoderm. Together, these data demonstrate the multiple differentiations potential of PMSCs in vitro, which confers potential use in serving as desirable cell types for lung injury regeneration.